Studies on Germination Behaviour of Seeds Harvested from Moringa Leaf Extract Sprayed Rauvolfia serpentina Plants - Singh, Pankaj; Pattanaik, Swapnendu; Chawhaan, Pravin H.; Suman Goud, B. (Indian Forester, 2024)
Natural biostimulants hold lot of potential in organic cultivation of medicinal plants, especially in those medicinal plants showing low to moderate seed germination. Rauvolfia serpentina is an economically important medicinal crop due to its root commercial value. However, stony coat and low seed quality imposes low to moderate seed germination in this plant. An organic approach is very essential to improve the plant health which leads to the production of good healthy seeds with high germination percentage. Moringa oleifera leaf extract (MLE) has been widely used as natural biostimulant for the improvement of crop growth and productivity. Thus, the present study was undertaken to assess the germination behaviour of harvested seeds from MLE sprayed R. serpentina plants. The field experiment was established under Randomized Block Design and plants were foliar sprayed with different doses of aqueous MLE i.e. 3.0%-21.0% for one year. Mature seeds were harvested and subjected to germination test to record germination percentage (G%), mean germination rate (MGR), mean germination time (MGT) and germination index (GI). The study revealed that seeds collected from 12% MLE sprayed R. serpentina plants have significant higher germination percentage (80), MGT (8.72), MGR (0.117), and GI (6.90) followed by 9% of MLE sprayed plants as compared to control. Thus, the aqueous 9-12% MLE foliar doses showed potential as natural biostimulant for production of healthy R. serpentina seed with better germination percentage.